Population pharmacokinetics and probability of target attainment in patients with sepsis under renal replacement therapy receiving continuous infusion of meropenem: Sustained low‐efficiency dialysis and continuous veno‐venous haemodialysis. Issue 11 (4th May 2021) - Westermann, Isabella; Gastine, Silke; Müller, Carsten; Rudolph, Wiebke; Peters, Frank; Bloos, Frank; Pletz, Mathias; Hagel, Stefan
Abstract : Aims: To describe the population pharmacokinetics (PK) and probability of target attainment (PTA) of continuous infusion (CI) of meropenem in septic patients receiving renal replacement therapy (RRT). Methods: Fifteen patients without RRT, 13 patients receiving sustained low‐efficiency dialysis and 12 patients receiving continuous veno‐venous haemodialysis were included. Population PK analysis with Monte Carlo simulations for different dosing regimens was performed. For minimum inhibitory concentration 2 mg/L was chosen. The target was set as 50% time ≥4× minimum inhibitory concentration. Results: The PK of meropenem was best described by a 1‐compartment model with linear elimination. Serum creatinine, residual diuresis and time on RRT, with no difference between sustained low‐efficiency dialysis and continuous veno‐venous haemodialysis, were found to be significant covariates affecting clearance, explaining >20% of the clearance between subject variability. PTA analysis showed that in patients with RRT, 2 g/24 h, meropenem CI achieved a PTA of 95%. In patients without RRT, the target was achieved with 3 g/24 h CI or prolonged infusion of 1 g meropenem over 8 hours but not with bolus application of 1 g meropenem for 8 hours. Only 2 patients (both without RRT) had meropenem concentrations below the target level. However, approximately half of the patients with RRT receiving CI 3 g/24 h meropenem had toxic concentrations. Conclusion: We found relevant PK variability for meropenem CI in septic patients with or without RRT, leading to a substantial risk for overdosing in patients with RRT. This finding highlights the strong demand for personalized dosing in critically ill patients.